2012
DOI: 10.1016/j.acra.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Corpus Callosum Atrophy in Early Stage of Alzheimer’s Disease

Abstract: Rationale and Objectives Magnetic resonance imaging (MRI) studies reveal that the atrophy of the corpus callosum (CC) is involved in early Alzheimer’s disease (AD). This study investigates when and how the callosal change occur in the early course of AD. Materials and Methods High-resolution structural MRI were obtained from 196 old people, subjects were characterized using the Clinical Dementia Rating (CDR), 98 healthy controls were nondemented (CDR 0), 70 patients had a clinical diagnosis of AD in very mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…The CC on the midsagittal plane (MSP) was segmented using a previously described semi-automatic method [15]. The method consists of the following 3 steps:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CC on the midsagittal plane (MSP) was segmented using a previously described semi-automatic method [15]. The method consists of the following 3 steps:…”
Section: Methodsmentioning
confidence: 99%
“…Most previous studies [5,6,7,8,9,10,11,12,13,14,15] have focused on the investigation of CC atrophy using cross-sectional data, in which intersubject variance is inevitable. However, the analysis of longitudinal data can reduce the impact of intersubject variance by measuring changes within individuals relative to their own baselines, and this type of analysis can also control for differences associated with cross-sectional data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results from previous studies have been inconsistent. Some studies revealed a smaller CC size in patients with AD compared with healthy controls (Gootjes et al, 2006;Li et al, 2008;Wiltshire et al, 2005); some found a smaller anterior region of the CC (Thomann et al, 2006;Zhu et al, 2012); and others found a smaller posterior the CC (Hanyu et al, 1999;. There were also studies reporting no relationships between AD and total CC size (Kaufer et al, 1997;Thompson et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…The CC atrophy and structural changes have been found by using the region of interest (ROI) analysis in patients with AD (Di Paola et al, 2010a;Frederiksen et al, 2011;Zhu et al, 2012Zhu et al, , 2014, and some of these studies have revealed that the decrease in the CC midsagittal crosssectional area was independently associated with the progression of AD. It was speculated that the decrease in the CC area might be due to the loss of callosal fibers (Aboitiz et al, 1992;Riise and Pakkenberg, 2011).…”
Section: Introductionmentioning
confidence: 99%